Faktor Risiko Indeks Massa Tubuh (IMT) dan Faktor Risiko Lain terhadap Kejadian Diabetes Melitus pada Lansia - Harjatmo, Titus Priyo; Astuti, Trina; Nugroho, Alfiantani (JURNAL RISET GIZI, 2023)
Background: Diabetes melitus (DM) is a metabolic diseases with medical conditions indicated by an increase in blood glucose levels exceeding normal that occurs due to abnormalities in insulin secretion, insulin action or both. Data on elderly morbidity in South Jakarta 2020 states that 12.78% of elderly population suffers from DM.Objective: To determine the risk factors for Body Mass Index (BMI) and other risk factors for the incidence of DM in the elderly at Puskesmas Pancoran in 2020-2021.Method: This study analyzed secondary data with cross sectional approach. Sample of this study was elderly patients who did checkups at the Pancoran Health Center, South Jakarta in 2020-2021, was taken using purposive sampling in total of 97 samples. Risk analysis using Mantel Haenszel test by looking at the odds ratio.Results: The results showed that age and gender were protective factors that could reduce the risk of 0.606 times (95% CI: .258 – 1.468) and 0.915 times (95% CI: 0.400 – 2.093) of the DM. Meanwhile, BMI and daily sugar consumption were significant risk factors for DM. BMI 2.6 times (95% CI: 1,089 - 6,417) more at risk of developing DM and the amount of sugar consumption per day >4 tablespoons 4.1 times (95% CI: 1,749 - 9,711) more at risk of developing DM.Conclusion: Body mass index ≥25 kg/m2 and total sugar consumption >4 tablespoons (>50 grams) a day are significant risk factors for diabetes mellitus in the elderly.